The Relation of Personal Hygiene with The Incidence of Scabies at Al Falah Male Boarding School Students Sub-district of Liang Anggang in the Year 2016 - Nur Muafida; Imam Santoso; Darmiah Darmiah (State Islamic University of Sunan Ampel, 2017)
Poor personal hygiene can be a factor supporting the development of skin diseases such as scabies. In Indonesia the scabies disease numerous in boarding school. One of the things that support the transmission of scabies is personal hygiene students who are not good. The study aimed to determine the relationship of personal hygiene with the incidence of scabies on students Al Falah male boarding school students at sub-district of Liang Anggang in the year 2016. This research is an analytic observational with cross sectional design. The sample of research are students of Al Falah for boys boarding school Sub-district of Liang Anggang as many as 127 people. Data analysis using statistical Chi-square test (X2). The results showed among 127 students, 59 of them in a poor condition of personal hygiene 53 of them categorized affected with scabies (89.8 %). While the remaining 68 students were in a good condition of personal hygiene with 23 of them having scabies (33.8%). X2 test results showed that there was a significant relationship, personal hygiene with the incidence of scabies on students boarding school Al Falah for boys Sub-district of Liang Anggang in the year 2016 at p-value = 0.000. Efforts should be made to reduce the incidence of scabies among others: showering twice a day using clean water, use personal belongings are not mutually borrowing, keep clean hands and nails, hygiene clothing and cleanliness of the bed.